Solve the equation -2(y - 1) = 9.

-11/2

7/2

11/2

-7/2

-11/2

7/2

11/2

-7/2

-11/2

7/2

11/2

-7/2

Asked
1 year ago

Viewed
853897 times

Hope this helps !! Did it step by step

**Answer:**

-7/2

**Step-by-step explanation:**

Use distributive property: a(b +c) = a*b +a*c

-2(y-1) = 9

y*(-2) - 1*(-2) = 9

-2y + 2 = 9 **{Subtract 2 from each side}**

-2y = 9 - 2

-2y = 7 **{Divide each side by -2}**

y = 7/-2

**y = -7/2**

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email